The combination of zalfermin and semaglutide has additive therapeutic effects in a diet-induced obese and biopsy-confirmed mouse model of MASH - Jenny Norlin; Maria Dermit; Nikos Sidiropoulos; Elisabeth D. Galsgaard; Henrik H. Hansen; Michael Feigh; Sanne S. Veidal; Markus Latta; Emma Henriksson; Birgitte Andersen (PLoS ONE, 2025)
Fibroblast growth factor 21 (FGF21) analogs have significant therapeutic potential in metabolic dysfunction–associated steatohepatitis (MASH) but limited body weight effects in patients with MASH. This study investigated the effect of combined treatment with the FGF21 analog zalfermin and the glucagon-like peptide-1 receptor agonist semaglutide on body weight and plasma and liver biochemistry and histology in a mouse model of MASH. Amylin liver nonalcoholic steatohepatitis diet-induced obese-MASH mice with biopsy-confirmed MASH and fibrosis were administered (subcutaneous [SC], daily [QD]) vehicle, zalfermin (0.05 or 0.2 mg/kg), semaglutide (3 or 120 µg/kg), or zalfermin 0.05 mg/kg + semaglutide 3 µg/kg for 8 weeks (n = 11–12 per group). Vehicle-dosed (SC, QD) chow-fed mice served as normal controls (n = 10). Pre- to post-liver biopsy histology was compared for within-subject evaluation of changes in non-alcoholic fatty liver disease Activity Score (NAS), fibrosis stage, and quantitative histology. Additional endpoints included plasma/liver biochemistry and liver RNA sequencing. Combined low-dose zalfermin and semaglutide treatment resulted in super-additive body weight loss (−18%) vs. individual low-dose monotherapies (zalfermin, −6%; semaglutide, −4%) and was equally effective as high-dose zalfermin monotherapy (−16%) and semaglutide (−15%). Low-dose combination therapy promoted greater benefits on transaminases, total cholesterol and triglycerides, NAS, steatosis, and inflammation vs. individual low-dose monotherapies and high-dose semaglutide, and high-dose zalfermin was as effective as the low-dose combination therapy on most endpoints. Combination treatment reduced gene expression markers of fibrosis to a greater degree than monotherapies. In conclusion, combined low-dose zalfermin and semaglutide, as well as high-dose zalfermin, resulted in beneficial effects on body weight and biochemical and histological endpoints, supporting the clinical development of zalfermin as therapy for patients with MASH.